2023
DOI: 10.3390/jpm13060946
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Radiotherapy Workflow for Head and Neck Cancer with Artificial Intelligence: A Systematic Review

Abstract: Background: Head and neck cancer (HNC) is characterized by complex-shaped tumors and numerous organs at risk (OARs), inducing challenging radiotherapy (RT) planning, optimization, and delivery. In this review, we provided a thorough description of the applications of artificial intelligence (AI) tools in the HNC RT process. Methods: The PubMed database was queried, and a total of 168 articles (2016–2022) were screened by a group of experts in radiation oncology. The group selected 62 articles, which were subdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Nevertheless, a recent systematic review by Franzese et al 10 found that AI research in radiotherapy is still in its infancy, and most of the studies performed to date have primarily focused on the contouring process. As those authors observed, more research is needed to better understand the potential use of AI for planning, optimization and delivery 10 …”
Section: Image‐based Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, a recent systematic review by Franzese et al 10 found that AI research in radiotherapy is still in its infancy, and most of the studies performed to date have primarily focused on the contouring process. As those authors observed, more research is needed to better understand the potential use of AI for planning, optimization and delivery 10 …”
Section: Image‐based Analysismentioning
confidence: 99%
“…AI has the potential to improve head and neck surgery in many different ways, but especially by improving the analysis of medical imaging, voice samples, gene expression and clinical data 4 . AI can be applied in a wide range of different areas, including robotic surgery, 5–8 radiotherapy, 9,10 clinical oncology, 11 radiology, 12–17 nursing, 18–20 pathology, 6,21–23 phoniatrics 24 and molecular biology 25–28 . AI has been used to develop prediction models based on the analysis of existing data sets to predict cancer progression, 29 overall survival stratification, 30 lymph node metastases, 31,32 treatment‐related toxicity 11 and hospital stay length 33 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations